PERLINDUNGAN HUKUM TERHADAP KORBAN BODY SHIMMING DI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Kinaria Afriani; Putri Sari Nilam Cayo (Fakultas Hukum Universitas IBA Palembang, 2023)
ABSTRACT Body shaming is a case that has been going on for quite a long time in the western part of the world. Body shaming also causes individuals who experience it to be more sensitive to the rejection that occurs when we pay more attention to their bodies because they do not conform to the ideal standards of society. Initially, body shaming only became a trend for jokes, but over time it became serious to the point of bringing down or vilifying other people, causing discomfort to the person who was the object of body shaming. The type of research that the author uses is normative juridical, which is a method that focuses on research on library data, or secondary data through legal principles and legal comparisons. Basically, body shaming insults carried out through social media are criminal acts whose perpetrators can be subject to criminal sanctions under Article 27 paragraph (3) jo and Article 45 paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions (